Small-scale irrigation for food security in sub-Saharan Africa - Tafesse, Mekuria (Technical Centre for Agricultural and Rural Cooperation, 2003)
This study visit is largely the result of discussions held at a seminar on Private irrigation in sub-Saharan Africa – Regional seminar on Private sector participation and irrigation expansion in SSA, co-organised by the International Water Management In